Jóvenes imprudentes: conducta peligrosa y juventud liminal en Nueva España - Lipsett-Rivera, Sonya (Anuario de Historia de América Latina, 2025)
Eighteenth-century transformations in the ideas about manliness in New Spain gave rise to the perception of scandalous behaviour among the sons of elite families. These young men partied, drank to excess, gambled, womanized, and refused any respectable occupations—all activities that previously had been dismissed as the “folly of youth.” Where dangerous conduct within the period of liminal youth, from the ages of 20 to 25, had previously been tolerated, new ideas about masculinity made such actions a threat to family honour. Changes in vagrancy laws in the eighteenth century allowed families to use the state to discipline their offspring and supress the scandals. Families denounced their sons thus allowing themselves to take the high moral ground and to contain the scandal of their sons’ conduct. Using the ideas of Ari Adut, I explore the logic of the denunciations and their use by elite families in New Spain in order to understand the radical departure of conceptions of scandals among elite families and their deployment of vagrancy denunciations.
Keywords: Masculinity; Scandal; Mexico; Vagrancy.